FEMINISM OF THE MAIN CHARACTER IN THE BIRD BOX MOVIE - Vinka Andriani; Ratna Sari Dewi (PROJECT (Professional Journal of English Education), 2024)
Feminism is a movement that fights for women's rights to have an equal position with men without any differences in all areas of life. A movie is a popular mass medium that lucidly presents images to audiences. The main character is the most important character who is the core of the story or the story's point of view. The purpose of this research is to find: 1) the kind of feminism that exists in the main character; 2) the feminism values contained in the main character; and 3) the characterization of the main character. This research uses a qualitative descriptive method. In collecting data, researchers watched the film, read and viewed all the sources, then recorded and analyzed them. This research found two types of feminism, namely liberal feminism and existential feminism, and then four feminism values, namely independence, gender equality, freedom, and solidarity. Finally, four characterizations were found, namely firmness, leadership, toughness, and personality.